การจัดการเงินทุนของการประปานครหลวง - โสภาพรรณ ลุลิตานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 1982)
The Metropolitan Water Works Authority (MWWA) is a non-profit-making organization. Funds management of the organization is of great interest. Owning to the growth of population, the MWWA has to face with the ever-increasing demand for more water supply. As a result, the Master Plan, a long-term project of 30 years, was set up. The purpose of the Master Plan was to present estimates of population and water requirements up to the year 2000 and to recommend additional water supply, treatment and distribution facilities. It comprises three stages of operation.The main purpose of this thesis is to examine the funds management of the first stage of the Master Plan during the fiscal year 1977-1986. The first stage of operation is composed of two phases, namely, the Phase I project and the Phase II project. The study also reviews the investment expenditures of the two projects and the pipe replacement program, sources of funds and the considerations in choosing them, and the analysis of financial position of the MWWA. From the study, it is found that most of the funds employed are financed by long-term loans from both public and private sectors. Evidently, the costs of loans from private sector are higher than those from public sector. The government also provide funs for the MWWA in terms of subsidy and equity.